2014
DOI: 10.1177/1090820x14539972
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility of Reduction Mammaplasty Assessed for the Brazilian Public Health System

Abstract: Reduction mammaplasty performed in the Brazilian national health care system provides a cost-utility ratio equivalent to approximately £142 per 1 quality-adjusted life year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 34 publications
(52 reference statements)
1
14
0
2
Order By: Relevance
“…Reduction mammoplasty (RM) is commonly performed to both reduce breast weight and volume and reposition the breasts, which improves the HRQoL of the patient. Several randomized studies have demonstrated the effectiveness and cost-effectiveness of RM (1, 4, 5). The procedure is also reported to increase HRQoL regardless of the patient’s body mass index (BMI) (6).…”
Section: Introductionmentioning
confidence: 99%
“…Reduction mammoplasty (RM) is commonly performed to both reduce breast weight and volume and reposition the breasts, which improves the HRQoL of the patient. Several randomized studies have demonstrated the effectiveness and cost-effectiveness of RM (1, 4, 5). The procedure is also reported to increase HRQoL regardless of the patient’s body mass index (BMI) (6).…”
Section: Introductionmentioning
confidence: 99%
“…A significant portion of the Brazilian population depends on the Brazilian public health system (Sistema Único de Saúde - SUS), which is often the only option for women with breast hypertrophy. Araújo et al studied the cost-utility relationship of reduction mammoplasty performed by the SUS and found that there was a positive relationship, justifying the need to mobilize resources for this type of procedure ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, few Brazilian studies have been published on health economics, 5,7,28,36,40 and none of them related to spine care in neurosurgery or orthopedics. Some countries have established that thresholds of what should be cost-effective: $50,000.00-$100,000.00 per QALY in the US, 41 Can$20,000.00-$40,000.00 in Canada, 23 and £20,000.00-£30,000.00 in the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it must be noted that the utility gain for patients from public and private health care systems would not be similar. 5 To date, there have been no published data on utility gain after LDH surgery in the Brazilian public health care system. Future studies are needed to address this issue and provide data on economic evaluation of LDH treatment in the Brazilian public health care system.…”
Section: Discussionmentioning
confidence: 99%